Biomonitoring of toxic and potentially toxic trace elements in the urine of residents of an industrial region - Onul, N.M.; Yuntunen, H.M.; Rodionova, V.V.; Biletska, E.M.; Polion , M.Iu.; Turenko , O.A. (Medicni Perspektivi, 2025)
The problem of the influence of environmental heavy metals on the human body is extremely relevant. At the same time, the study of trace element status under the influence of environment and during various pathological processes in the body using modern biomonitoring methods is increasingly used as a tool for risk assessment, risk communication and decision-making on public health risk management. The purpose of the work was to determine the concentration and gender-age characteristics of the content of toxic and potentially toxic trace elements from the group of heavy metals in the urine of clinically healthy residents of the industrial region and patients with pyelonephritis. To achieve the goal, the content of toxic and potentially toxic trace elements – aluminum, lead, barium, cadmium and strontium - was determined in the urine of 108 residents of the Dnipropetrovsk region - clinically healthy individuals and patients with pyelonephritis during 2022-2024. It was established that the content of toxic and potentially toxic metals in the urine of conditionally "healthy" residents of the industrial region fluctuates in a wide range, cadmium concentration in the urine of the inhabitants of the region corresponds to the reference values, however it exceeds them in terms of aluminum, barium, lead and strontium content. The content of such xenobiotics as lead, cadmium and barium is 1.4-14.2 times higher than the data of studies conducted in the territory of the ecological-geochemical optimum according to the maximum and average indicators, which indicates their technogenic origin. Concentrations of barium, cadmium, lead, and strontium in urine of men is higher than in women, with lower levels of aluminum. The development of diseases of the urinary system is accompanied and may be aggravated by microelement imbalance, which is manifested by a significant increase in the concentration of aluminum and cadmium by 1.4-1.7 times with a decrease in the content of barium. During kidney diseases development adaptation of the organism was defined as a stage of tension and was related to the duration of the disease. The obtained results are an important basis for the further development of the national base of reference values for microelements content in the biosubstrates during biomonitoring for the timely diagnosis of microelement dyshomeostasis and the implementation of a set of measures to improve public health.